Association of sulfur amino acid consumption with cardiometabolic risk factors: Cross-sectional findings from NHANES III. (February 2020) - Dong, Zhen; Gao, Xiang; Chinchilli, Vernon M.; Sinha, Raghu; Muscat, Joshua; Winkels, Renate M.; Richie, John P.
Abstract: Background: An average adult American consumes sulfur amino acids (SAA) at levels far above the Estimated Average Requirement (EAR) and recent preclinical data suggest that higher levels of SAA intake may be associated with a variety of aging-related chronic diseases. However, there are little data regarding the relationship between SAA intake and chronic disease risk in humans. The aim of this study was to examine the associations between consumption of SAA and risk factors for cardiometabolic diseases. Methods: The sample included 11, 576 adult participants of the Third National Examination and Nutritional Health Survey (NHANES III) Study (1988–1994). The primary outcome was cardiometabolic disease risk score (composite risk factor based on blood cholesterol, triglycerides, HDL, C-reactive protein (CRP), uric acid, glucose, blood urea nitrogen (BUN), glycated hemoglobin, insulin, and eGFR). Group differences in risk score by quintiles of energy-adjusted total SAA, methionine (Met), and cysteine (Cys) intake were determined by multiple linear regression after adjusting for age, sex, BMI, smoking, alcohol intake, and dietary factors. We further examined for associations between SAA intake and individual risk factors. Findings: Mean SAA consumption was > 2.5-fold higher than the EAR. After multivariable adjustment, higher intake of SAA, Met, and Cys were associated with significant increases in composite cardiometabolic disease risk scores, independent of protein intake, and with several individual risk factors including serum cholesterol, glucose, uric acid, BUN, and insulin and glycated hemoglobin ( p < 0.01). Interpretation: Overall, our findings suggest that diets lower in SAA (close to the EAR) are associated with reduced risk for cardiometabolic diseases. Low SAA dietary patterns rely on plant-derived protein sources over meat derived foods. Given the high intake of SAA among most adults, our findings may have important public health implications for chronic disease prevention. Funding: This study does not have any funding.